2008
DOI: 10.1007/bf03345607
|View full text |Cite
|
Sign up to set email alerts
|

Is resistin a link between highly active antiretroviral therapy and fat redistribution in HIV-infected children?

Abstract: Fat redistribution occurred in most HIV-infected children undergoing PI therapy. Because serum resistin levels reflect the amount of visceral fat, they could be considered a sensitive marker of fat redistribution in HIV-infected children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…Similarly, there is no consensus on resistin's role in metabolic dysregulation. Some investigators have shown a significant increase in circulating resistin after chronic alcohol exposure (59) and after HIV infection/ART regimen (28,48). In nonhuman primates, resistin levels have been shown to increase shortly after SIV infection when animals are fed an atherogenic diet before SIV inoculation.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, there is no consensus on resistin's role in metabolic dysregulation. Some investigators have shown a significant increase in circulating resistin after chronic alcohol exposure (59) and after HIV infection/ART regimen (28,48). In nonhuman primates, resistin levels have been shown to increase shortly after SIV infection when animals are fed an atherogenic diet before SIV inoculation.…”
Section: Discussionmentioning
confidence: 99%
“…It has also been associated with unfavorable changes in body composition (lipodystrophy), which may occur de novo in untreated HIV-infected patients, but is more often seen in those receiving PIs. The accompanying increase in visceral fat is likely to contribute to IR, perhaps mediated by heightened production of resistin [9] and/or reduced production of adiponectin [10] by adipose tissue. Several studies have now established that direct inhibition of the insulin-responsive facilitative glucose transporter isoform 4 (GLUT4) is a primary mechanism by which PIs and NRTIs acutely alter peripheral glucose disposal [8].…”
Section: Introductionmentioning
confidence: 99%
“…Increases in leptin may also be explained by so‐called leptin resistance [23]. Furthermore, the increase in circulating resistin levels may reflect fat redistribution, as it has been found to correlate with the amount of visceral fat [24]. However, we did not find an association of leptin or resistin with lipodystrophy or HOMA values, which only increased during the first year on HAART.…”
Section: Discussionmentioning
confidence: 53%